Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover Dan Net Profit Margin Terhadap ROA Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019 - Nilam Permata Sari Br Tarigan; Febby Chintya; Grace Elisabeth; Mila Yulia Herosian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the variable current ratio, debt to equity ratio, total asset turnover and net profit margin on ROA. The population of this study obtained 67 companies selected using purposive sampling with certain criteria as many as 27 companies. The type of data used in this research is quantitative data. The data source in this research is secondary data. The data collection technique is done by using documentation technique and data analysis using multiple linear analysis. The results of the study partially show that the current ratio, total asset turnover and net profit margin have a positive and significant effect on ROA, the debt to equity ratio has a negative and significant effect on ROA. The research results simultaneously show the current ratio, debt to equity ratio, total asset turnover and net profit margin to ROA. Keywords: Current Ratio, Debt To Equity Ratio, Net Profit Margin, ROA, Total Assset Turnover